Drying and analysis of waste from potatoes, carrots, and chayote for food purposes - Matias Silva, Nayane; Gonçalves Souza, Diene; Alves Mesquita, Abner; Cabral de Oliveira, Daniel Emanuel; Resende, Osvaldo; Antônio Pereira da Silva, Marco (Comunicata Scientiae, 2023)
Vegetable peels are rarely used in food preparation, causing the loss of several nutrients. Such residues ca produce flour as a possible food source with added nutritional and economic value. Thus, the objective was to evaluate the nutritional quality and the color of the flours obtained from the peels of potato, carrot, and chayote subjected to drying at the temperatures of 40, 50, 60, and 70 °C, as well as analyzing the drying kinetics. The peels were removed, packed in an isothermal box with ice, and taken to the laboratory. Then they were washed in running water to remove dirt and unwanted parts and sanitized. After this stage, they were broken into 2 cm lengths. The drying was carried out in 150 g of peels in triplicate for each raw material. Subsequently, nutritional quality, color, and drying models were determined. Flours obtained from drying at higher temperatures showed higher protein content and lower lipid content. The higher the temperature, the shorter the drying time for the flour. All flours presented excellent nutritional quality. Among the models studied for potato peels, Wang and Singh, Midilli, and Logarithmic are the most suitable. For chayote and carrot peels, the Midilli model is the most adequate. Using vegetable residues added to food formulations presents itself as an excellent nutritional source, besides adding flavor and texture to foods.